PENGARUH PEMERIKSAAN PAJAK DAERAH TERHADAP PENERIMAAN PAJAK DAERAH DI KOTA TANGERANG SELATAN - Reza Kurniawan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
This study aims to determine the influence as well as potential inspection of Local Taxes on the receipt of Regional Taxes in the City of South Tangerang. After the tax audit, the Local original Income increases further, as seen from the level of compliance of taxpayers who comply with reporting and paying taxes on time and exact amount. This is expected by the South Tangerang City Government.